Intra-Individual Variation in the Jump Smash for Elite Malaysian Male Badminton Players - Yuvaraj Ramasamy; Yeap Ming Wei; Harley Towler; Mark King (Applied Sciences)
The badminton jump smash is vital for winning rallies, but players can have unintended variations in performance. This study examines the causes of intra-individual smash speed variations among 19 Malaysian male elite players. Twenty-five jump smashes were recorded using a 3D motion capture system, with the three fastest (95.0 ± 3.6 m·s−1) and three slowest (85.8 ± 5.8 m·s−1) smashes per participant categorised into different groups. Six racket/shuttlecock variables and six upper body technique variables during the swing phase and at the point of contact were analysed. Five out of the six racket/shuttlecock variables, including post-impact shuttlecock speed, racket head speed at contact, impact location, distance from the racket’s geometric centre, and swing time, significantly differed between groups. Only the shoulder elevation angle differed significantly from 75% to 95% of the forward swing (p = 0.023), with less elevation during faster smashes. Consistency in producing high shuttlecock speeds during the jump smash for elite players is primarily achieved through variables linked to timing. Players/coaches should focus on being able to initially produce high racket head speeds, at which point ensuring a consistently efficient impact between the stringbed and shuttlecock should be the priority.